Lithium Ferrite as the Cathode of the Electrochemical Power Sources: the Perspectives of Sol-gel Synthesis Method - O.M. Uhorchuk; V.V. Uhorchuk; M.V. Karpets; L.S. Kaykan; B.Ja. Deputat; A.M. Boychuk; M.I. Hasyuk (Журнал нано- та електронної фізики)
Synthesis of highly dispersed systems of lithium-ferrite oxide spinel, obtained by the low-temperature sol-gel method, with the subsequent auto combustion and the comparison of these systems’ characteristics with the analogous ones of the conventional ceramic method are performed. It is shown that the systems synthesized by solid-phase and sol-gel methods are the single phase structures with the space group P4332. The sol-gel method of auto combustion made it possible to increase the size of crystallites in more than 4 times and the specific area of the surface in 20 times. Obtained by sol-gel method lithium pentaferrit is suggested to be used as the cathode of lithium power sources.